Alpha- and betacoronavirus cis-acting RNA elements - Madhugiri, Ramakanth; Nguyen, Hoang Viet; Slanina, Heiko; Ziebuhr, John; Justus Liebig University Giessen (My University, 2024)
Coronaviruses have exceptionally large RNA genomes and employ multiprotein replication/transcription complexes to orchestrate specific steps of viral RNA genome replication and expression. Most of these processes involve viral cis-acting RNA elements that are engaged in vital RNA–RNA and/or RNA–protein interactions. Over the past years, a large number of studies provided interesting new insight into the structures and, to a lesser extent, functions of specific RNA elements for representative coronaviruses, and there is evidence to suggest that (a majority of) these RNA elements are conserved across genetically divergent coronavirus genera. It is becoming increasingly clear that at least some of these elements do not function in isolation but operate through complex and highly dynamic RNA–RNA interactions. This article reviews structural and functional aspects of cis-acting RNA elements conserved in alpha- and betacoronavirus 5'- and 3'-terminal genome regions, focusing on their critical roles in viral RNA synthesis and gene expression.
Keywords: ddc:610